1974
DOI: 10.6028/jres.078a.012
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of fluorocarbon ions in C2F6. Implications for the radiolysis

Abstract: Reacti ons of the fragment ions formed in the photoionization of C,F., Xe-C,F., and Kr-C 2F. mixtures have been investigated in th e NBS photoion ization mass spectrometer usin g both helium (21.2 eV) and neo n (16_66-16_84 eV) resonance radiation_ Contrary to previously held views , it is shown that CF i ions havin g no internal excitation energy undergo the F -tran sfer reaction :A rate constant of 4 ± 1 X lO -" cm 3/molecule -s is determined for reaction (a) at press ures below 10 -2 torr_ On the basis of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

1977
1977
1996
1996

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…Using a highpressure mass spectrometer, Pabst et al28 measured a rate constant of 3.3 X 10™m cm3 s'1 at 323 K for reaction 1 and noted evidence for internally excited CF+, produced by electron impact on CF4.Richter and Lindinger29 measured a rate constant upper limit of <5 X 10™12 cm3 s'1 for reaction 1 at 0.05-eV center-of-mass collision energy in a drift tube experiment at 300 K, in agreement with the present results for the slow-reacting state of CF*. Rate constants of ~1.9 X 10"10 and 3.94 X 10™" cm3 s™1 were measured for reaction 2 by Sieck et al32 and Marcotte and Tiernan,33 respectively. The value of Sieck et al is reported as an estimate due to poorly known ion residence time.…”
supporting
confidence: 88%
“…Using a highpressure mass spectrometer, Pabst et al28 measured a rate constant of 3.3 X 10™m cm3 s'1 at 323 K for reaction 1 and noted evidence for internally excited CF+, produced by electron impact on CF4.Richter and Lindinger29 measured a rate constant upper limit of <5 X 10™12 cm3 s'1 for reaction 1 at 0.05-eV center-of-mass collision energy in a drift tube experiment at 300 K, in agreement with the present results for the slow-reacting state of CF*. Rate constants of ~1.9 X 10"10 and 3.94 X 10™" cm3 s™1 were measured for reaction 2 by Sieck et al32 and Marcotte and Tiernan,33 respectively. The value of Sieck et al is reported as an estimate due to poorly known ion residence time.…”
supporting
confidence: 88%
“…The finding of an appreciable efficiency for the deprotonation reaction of CF 3 C 6 H 6 + ions by benzene (efficiency = 32%) under ICR conditions prompted us to use the trifluoromethylation reaction by radiolytically formed CF 3 + as a convenient way to point out and study the proton transfer between truly ground state arenium ions and benzene. The trifluoromethylation of benzene by CF 3 + ions under radiolytic conditions is a well-characterized ionic process, 15a,n where the ionic reactant and intermediates may attain thermal equilibration by unreactive collisions with the bulk gas before undergoing reaction.…”
Section: Resultsmentioning
confidence: 99%
“…However, it should not be taken for granted that the high-pressure radiolytic medium does ensure fast thermal equilibration of reactive intermediates. For instance, this condition is not met in the trifluoromethylated arenium ions from CF 3 + attack to C 6 D 5 CH 2 CH 2 C 6 H 5 undergoing fast multiple H + /D + transfer between the trifluoromethylated and the spectator ring 15d. In this system the proximity of the second phenyl ring promotes H + /D + transfer from the CF 3 -substituted arenium ring before the latter had a chance to dissipate its excess energy by unreactive collisions, initiating an extensive sequence of interannular H/D exchange.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations